Spread of SARS-CoV-2 Infection in Adult Populations in Cameroon: A Repeated Cross-Sectional Study Among Blood Donors in the Cities of Yaoundé and Douala - Arsène Brunelle Sandie; Françoise Ngo Sack; Christiane Ingrid Medi Sike; Joseph Mendimi Nkodo; Hortense Ngegni; Haverie Ghislaine Ateba Mimfoumou; Sarah Audrey Lobe; Diane Choualeu Noumbissi; Fabrice Tchuensou Mfoubi; Paul Alain Tagnouokam Ngoupo; Lawrence Ayong; Richard Njouom; et al. (Journal of Epidemiology and Global Health, 2023)
Abstract Over a period of about 9 months, we conducted three serosurveys in the two major cities of Cameroon to determine the prevalence of SARS-COV-2 antibodies and to identify factors associated with seropositivity in each survey. We conducted three independent cross-sectional serosurveys of adult blood donors at the Central Hospital in Yaoundé (CHY), the Jamot Hospital in Yaoundé (JHY) and at the Laquintinie Hospital in Douala (LHD) who consented in writing to participate. Before blood sampling, a short questionnaire was administered to participants to collect their sociodemographic and clinical characteristics. We included a total of 743, 1202, and 1501 participants in the first (January 25–February 15, 2021), second (May 03–28, 2021), and third (November 29–December 31, 2021) surveys, respectively. The adjusted seroprevalence increased from 66.3% (95% CrI 61.1–71.3) in the first survey to 87.2% (95% CrI 84.0–90.0) in the second survey, and 98.4% (95% CrI 96.8–99.7) in the third survey. In the first survey, study site, participant occupation, and comorbid conditions were associated with SARS-CoV-2 seropositivity, whereas only study site remained associated in the second survey. None of the factors studied was significantly associated with seropositivity in the third survey. Together, the data suggest a rapid initial spread of SARS-CoV-2 in the study population, independent of the sociodemographic parameters assessed.